GelMA, Click-Chemistry Gelatin and Bioprinted Polyethylene Glycol-Based Hydrogels as 3D Ex Vivo Drug Testing Platforms for Patient-Derived Breast Cancer Organoids - Nathalie Bock; Farzaneh Forouz; Luke Hipwood; Julien Clegg; Penny Jeffery; Madeline Gough; Tirsa van Wyngaard; Christopher Pyke; Mark N. Adams; Laura J. Bray; Laura Croft; Erik W. Thompson; et al. (MDPI AG, 2023)
3D organoid model technologies have led to the development of innovative tools for cancer precision medicine. Yet, the gold standard culture system (Matrigel®) lacks the ability for extensive biophysical manipulation needed to model various cancer microenvironments and has inherent batch-to-batch variability. Tunable hydrogel matrices provide enhanced capability for drug testing in breast cancer (BCa), by better mimicking key physicochemical characteristics of this disease's extracellular matrix. Here, we encapsulated patient-derived breast cancer cells in bioprinted polyethylene glycol-derived hydrogels (PEG), functionalized with adhesion peptides (RGD, GFOGER and DYIGSR) and gelatin-derived hydrogels (gelatin methacryloyl; GelMA and thiolated-gelatin crosslinked with PEG-4MAL; GelSH). Within ranges of BCa stiffnesses (1-6 kPa), GelMA, GelSH and PEG-based hydrogels successfully supported the growth and organoid formation of HR+,−/HER2+,− primary cancer cells for at least 2-3 weeks, with superior organoid formation within the GelSH biomaterial (up to 268% growth after 15 days). BCa organoids responded to doxorubicin, EP31670 and paclitaxel treatments with increased IC50 concentrations on organoids compared to 2D cultures, and highest IC50 for organoids in GelSH. Cell viability after doxorubicin treatment (1 µM) remained >2-fold higher in the 3D gels compared to 2D and doxorubicin/paclitaxel (both 5 µM) were ~2.75-3-fold less potent in GelSH compared to PEG hydrogels. The data demonstrate the potential of hydrogel matrices as easy-to-use and effective preclinical tools for therapy assessment in patient-derived breast cancer organoids.